Factors Related to the Event of Malaria in Pregnant Women in Harapan Health Center - Virdia Safitri; Fachry Amal; Ika Wijayanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Malaria prevalence based on blood history in Indonesia in 2018 is 0.4% (Riskesdas, 2018). Data on pregnant women in Jayapura Regency in 2018 are 4,120 people. Of these, 132 were positively infected by malaria pregnant women (Dinkes District of Jayapura, 2018 - 2019). The purpose of the study was to determine the relationship batween knowledge, ANC compliance and parity with incidence of malaria in pregnant women at the Puskesmas Harapan. The study design was quantitative analytic with croos sectional approach with a total sample of 37 trimester II dan II pregnant women, with sampling techniques exachautive sampling and data analysis with chi-square test. The results showed that the knowledge variables (p = 0.140), ANC compliance (p = 0.873) and parity (p = 0.140). It can be concluded that there is no relationship between knowledge, ANC compliance and parity with the incidence of malaria in pregnant women at the Puskesma Harapan Key word: Malaria, Pregnant Women, Knowledge, ANC, Parity